CONTINUING PROFESSIONAL DEVELOPMENT OF SOCIAL WORKERS IN PRACTICE: AN EXPLORATIVE INVESTIGATION - September, Rose (Social Work/Maatskaplike Werk, 2010)
The paper starts with a brief autobiographical reflective narration of my own experience as a social worker. The purpose is to demonstrate and contextualise the interaction, change and inherent ambivalences in relation to my own experience of post-qualifying learning. I qualified as a social worker in 1978. My first employment was with the Department of Social Welfare (Coloured Affairs) in the Western Cape. During the first week of my induction I was introduced to two important people, my supervisor and the “In-service training manager” (ISTM). My supervisor was responsible for supervising my day to day workload. The ISTM was exclusively responsible for guiding and testing me on the content of a thick lever-arch file called the in-service training manual. The latter contained all the relevant legislation, policies and departmental procedures that I had to study and know before becoming a permanently employed social worker and public servant. Every Friday I would religiously go to the inservice training guru to be tested on the contents of the file. The ISTM was also kept informed by my supervisor about my performance on the job and would comment on my progress as indicated by my “stats”. The latter was a record of how many clients I had seen and what the results achieved on each of these were. This process would continue until the in-service training was satisfactorily completed.